2014
DOI: 10.3389/fimmu.2014.00163
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Individual Modules of the immunoglobulin heavy chain locus 3′ Regulatory Region

Abstract: The Igh locus undergoes an amazing array of DNA rearrangements and modifications during B cell development. During early stages, the variable region gene is constructed from constituent variable (V), diversity (D), and joining (J) segments (VDJ joining). B cells that successfully express an antibody can be activated, leading to somatic hypermutation (SHM) focused on the variable region, and class switch recombination (CSR), which substitutes downstream constant region genes for the originally used Cμ constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…There is no doubt that the 3′RR plays a key role in IgH locus regulation (39) but the role of the conserved quasi-palindrome and the hierarchy between the modules remained poorly understood. By comparing relevant KO mouse models, our study demonstrated that the 3′RR includes at least two functional modules: (i) the distal module, which includes the hs4 enhancer element; and (ii) the proximal module, defined as the 3′RR quasipalindrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that the 3′RR plays a key role in IgH locus regulation (39) but the role of the conserved quasi-palindrome and the hierarchy between the modules remained poorly understood. By comparing relevant KO mouse models, our study demonstrated that the 3′RR includes at least two functional modules: (i) the distal module, which includes the hs4 enhancer element; and (ii) the proximal module, defined as the 3′RR quasipalindrome.…”
Section: Discussionmentioning
confidence: 99%
“…In B-lineage precursors, a first contribution was assigned to CBEs, which have been proposed to facilitate interactions between locus distant regions (14,20,41,42). Deletion of hs5-7 CBEs downstream from the mouse 3′RR resulted in only a slight modification of D and V H use (16), suggesting a modest contribution of 3′ CBEs in VDJ joining, although it is not excluded that full deletion (including hs8) might have a more drastic effect (39). Once VDJ recombination is completed, the 3′RR and the promoter of the VDJ-rearranged segment continue to interact and then starts the actual 3′RR stepwise transcriptional activation by its distal module.…”
Section: Discussionmentioning
confidence: 99%
“…How the 3=RR can mediate its silencing activity is presently unknown and may involve a developmental stage-dependent interplay between the topological reorganization of the IgH locus, which may be modulated by CTCF insulators and transcription factor-mediated loops, posttranslational modifications of factors such as CTCF, and the 3=RR epigenetic modifications and recruitment of transcription factors and corepressors (48)(49)(50)(51). Interestingly, there is some evidence that the human ␤-globin locus control region can in some contexts repress gene expression through transcriptional interference, potentially involving transcripts initiating in flanking repetitive sequences and running through the ␤-globin locus (52).…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as YY1, PAX5, IKAROS, CTCF, and Cohesin play important roles in various aspects of long-range events at the IgH locus, including V(D)J recombination, CSR, and promoter/enhancer and enhancer/enhancer interactions (3)(4)(5)(6). Multiple CTCF binding elements (CBEs) were reported along the IgH locus.…”
mentioning
confidence: 99%
“…This entails a long-range control of multiple upstream I promoters (6,13). Gene-targeted deletion of individual enhancers had no effect on GL transcription (14-16).…”
mentioning
confidence: 99%